The Relationship between the Characteristics of the Doctor in Charge of Services and Compliance with the Completion of BPJS Health Patient Medical Resumes at Aisyiyah Hospital in Bojonegoro - Dewi Wulan Sari; Septin Maisharah Karyono; Pramono Apriawan Wijayanto; Afriza Umami (LPPM STIKes Muhammadiyah Ciamis, 2025)
A discharge summary summarizes a patient's entire period of care and treatment provided by health workers and related parties. The completion of medical resumes affects the process of submitting claims to the National Health Insurance program. Attending Physician is responsible for preparing the medical resumes. A preliminary study at Aisyiyah Hospital in Bojonegoro found that 74.08% of files had pending claims due to incomplete medical records. Research: This study aims to describe the relationship between the characteristics of the Attending Physician and the compliance in completing medical resumes for Social Security Agency for Health in the inpatient ward of Aisyiyah Bojonegoro Hospital. Methods: The method used in this research is a quantitative approach with data analysis conducted using the chi-square method. Results: The study showed that the majority of Attending Physician were classified as less compliant in filling out medical resumes. There was no relationship between the characteristics of gender, age, length of service, employment status, and Attending Physician experience with compliance in filling out medical resumes at Aisyiyah Bojonegoro Hospital. However, there was a significant relationship between the personality characteristic of the neuroticism dimension and compliance in filling out medical resumes. Conclusion: The majority of Attending Physician characteristics at Aisyiyah Bojonegoro Hospital are male, over 40 years old, have a working period of more than 40 years, hold employment status as organic doctors, and have completed their last education at a university in the East Java region.